\(A=\dfrac{x\sqrt{x}+2x-\left(x-1\right)\left(\sqrt{x}-2\right)-\sqrt{x}-6}{x-4}:\dfrac{\sqrt{x}+2-\sqrt{x}+2}{\sqrt{x}-2}\)
\(=\dfrac{x\sqrt{x}+2x-\sqrt{x}-6-x\sqrt{x}+2x+\sqrt{x}-2}{x-4}\cdot\dfrac{\sqrt{x}-2}{4}\)
\(=\dfrac{4x-8}{\sqrt{x}+2}\cdot\dfrac{1}{4}=\dfrac{x-2}{\sqrt{x}+2}\)
\(\left\{{}\begin{matrix}x-3y=10\\2x+y=-1\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x-3y=10\\6x+3y=-3\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x-3y=10\\7x=7\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=1\\y=-3\end{matrix}\right.\)